2018
DOI: 10.1002/cctc.201801365
|View full text |Cite
|
Sign up to set email alerts
|

UV Assisted High‐Efficient Synthesis of α‐Ketoamides using Air Promoted by A Non‐Metal Catalyst in Aqueous Solution

Abstract: Presented here is the first example of UV (λ=210 nm) promoted procedure proceeding in aqueous media at room temperature using ambient air as the oxidant for efficient synthesis of an array of α‐ketoamides of all types using a non‐metal catalyst N‐iodosuccinimide with a loading of 20 mol%. With UV, oxygen in the air was efficiently utilized as the green oxidant, some control experiments were carried out and a plausible mechanism was proposed, disclosing that in aqueous solution, the oxidation process was actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It is worth mentioning that these methods were executed using metal or metal-free catalysts, oxidants, and other reagents under different conditions. In recent years, few synthetic approaches for α-ketoamides have been reported using the customary substates via photo 16 or metal catalysis, 17 oxidation, 18 electrochemical, 19 and direct amidation processes. 20 Because of the bulk contribution to the chemical and biological fields, developing novel methods for the direct synthesis of α-ketoamides is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that these methods were executed using metal or metal-free catalysts, oxidants, and other reagents under different conditions. In recent years, few synthetic approaches for α-ketoamides have been reported using the customary substates via photo 16 or metal catalysis, 17 oxidation, 18 electrochemical, 19 and direct amidation processes. 20 Because of the bulk contribution to the chemical and biological fields, developing novel methods for the direct synthesis of α-ketoamides is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Although many such methods have been developed for the synthesis of oxamates, to the best of our knowledge, there have been a few reports regarding the production of primary oxamates. In the case of α-ketoamides, synthetic methods proposed to date have largely focused on the preparation of secondary and tertiary α-ketoamides from alkenes, alkynes, aryl ethanes, α-ketoaldehydes, α-keto acids, aryl methyl ketones, 1-arylethanols, α-hydroxy ketones, and other starting materials . In contrast, there are only a handful of examples concerning the synthesis of primary α-ketoamides.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Our previous studies reported the preparation of diverse α-ketoamides under clean and mild conditions from varying substrates including aryl methyl ketones. [11,12] Currently, there are two issues involved with the direct amidation. Firstly, although I 2 is employed as the catalyst, its loading almost reaches up to the stoichiometric ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In classical amidations with the addition of iodine (I 2 ), the amine is recognized as the reactant, and I 2 is almost presumed to play the catalytic role . Our previous studies reported the preparation of diverse α ‐ketoamides under clean and mild conditions from varying substrates including aryl methyl ketones . Currently, there are two issues involved with the direct amidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation